Development of polyvinyl chloride composites with enhanced mechanical properties using modified ceramic particles - Ademola, Adewumi Ojo; Oladele, Isiaka Oluwole; Oluyemi, Daramola Ojo; Oke, Samuel Ranti; Akinbamiyorin, Ilesanmi M.; Taiwo, Anuoluwapo Samuel (Springer, 2025)
The integration of ceramic particles into polyvinyl chloride (PVC) composites offers a promising approach and has garnered significant attention due to their potential for enhancing mechanical properties. This work investigated the development and characterization of PVC composites enhanced with modified ceramic particles. Ceramic particulates, clays, and other mineral rock materials (non-plastics) with activators were processed and incorporated into the PVC matrix at varying weight percentages (5–30 wt%) and particle sizes (40–80 µm). The ceramic–PVC mixtures were synthesized using hot compression molding under specific conditions of 75 MPa pressure and 160 °C temperature. Mechanical properties’ testing was conducted using ASTM D3039 standards, covering flexural, tensile, hardness, and impact tests for comprehensive characterization. Microstructural analysis was performed using scanning electron microscopy (SEM). Results indicated that ceramic reinforcement significantly enhanced the mechanical properties of PVC composites, with notable improvements in flexural strength, tensile strength, hardness, and impact resistance. Moreover, the impact of particle size was crucial, as microstructural analysis revealed improved interfacial bonding between ceramic particles and PVC matrix, particularly with finer particle sizes (40 µm), suggesting better stress transfer. The findings demonstrated that including modified ceramic particles can substantially improve the performance of PVC composites, making them suitable as high-strength construction tiles and impact-resistant flooring.
Keywords: 40 Engineering; 4016 Materials Engineering; Polymers